Influence of price and promotion on purchasing decisions at Cafe Obrol Coffee in Haji Nawi South Jakarta - Putri Jasmine; Novia Susanti (Central Research Institute for Agriculture (CeRIA), 2023)
The purpose of this study was to determine the effect of price and promotion on purchasing decisions at Cafe Obrol Kopi in Haji Nawi, South Jakarta. This type of research is quantitative. The sampling technique used the slovin formula and obtained a sample of 98 respondents. Analysis of this data using validity test, reliability test, classic assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study indicate that price has a significant effect on purchasing decisions with a coefficient of determination of 45.1% and the hypothesis test is obtained tcount > ttable or (7.323 > 1.985). Promotion has a significant effect on purchasing decisions with a coefficient of determination of 45.1% and hypothesis testing obtained tcount > ttable or (7.323 > 1.985). Price and promotion simultaneously have a significant effect on purchasing decisions with the regression equation Y = 10.800 + 0.333X1 + 0.430X2. The coefficient of determination is 45.1% while the remaining 54.9% is influenced by other variable factors and hypothesis testing is obtained by calculating Fcount > Ftable or (38.960 > 3.09).